Healthy Living: Diabetes Warning Signs - Linda B. Bobroff (EDIS)
Revised! FCS8577, a 1-page handout by Linda B. Bobroff, informs older adults of the risks of untreated diabetes, and provides a checklist of the warning signs of high blood glucose levels. Published by the UF Department of Family Youth and Community Sciences, August 2010.